Wrapping and Blocking of Influenza A Viruses by Sialylated 2D Nanoplatforms. Issue 12 (14th May 2021) - Bhatia, Sumati; Donskyi, Ievgen S.; Block, Stephan; Nie, Chuanxiong; Burdinski, Angelique; Lauster, Daniel; Radnik, Jörg; Herrmann, Andreas; Haag, Rainer; Ludwig, Kai; Adeli, Mohsen
Abstract: Inhibition of respiratory viruses is one of the most urgent topics as underlined by different pandemics in the last two decades. This impels the development of new materials for binding and incapacitation of the viruses. In this work, we have demonstrated that an optimal deployment of influenza A virus (IAV) targeting ligand sialic acid (SA) on a flexible 2D platform enables its binding and wrapping around IAV particles. A series of 2D sialylated platforms consisting graphene and polyglycerol are prepared with different degrees of SA functionalization around 10%, 30%, and 90% named as G‐PG‐SAL, G‐PG‐SAM, and G‐PG‐SAH, respectively. The cryo‐electron tomography (Cryo‐ET) analysis has proved wrapping of IAV particles by G‐PG‐SAM . A confocal‐based colocalization assay established for these materials has offered the comparison of binding potential of sialylated and non‐sialylated nanoplatforms for IAV. With this method, we have estimated the binding potential of the G‐PG‐SAM and G‐PG‐SAH sheets for IAV particles around 50 and 20 times higher than the control sheets, respectively, whereas the low functionalized G‐PG‐SAL have not shown any significant colocalization value. Moreover, optimized G‐PG‐SAM exhibits high potency to block IAV from binding with the MDCK cells. Abstract : Schematic representation of wrapping several virus particles by flexible functionalized graphene sheets via multivalent interactions. Graphene sheets are functionalized with sialic acid derivatives that can efficiently bind to the influenza A virus and wrap several virus particles in one sheet due to multivalent interactions between sialic acid derivatives with spike hemagglutinin trimeric proteins on the virus surface.